Green Synthesis of Silver Nanoparticles from Leaf Extract of Nyctanthes arbor-tristis L. and Assessment of Its Antioxidant, Antimicrobial Response - Mishra A.K.; Tiwari K.N.; Saini R.; Kumar P.; Mishra S.K.; Yadav V.B.; Nath G. (My University, 2025)
The UPLC-Q-TOF–MS/MS analysis of ethanol extract of leaf confirmed the presence of important flavonoids like rutin (RT 5.95), hesperidin (RT 5.99), quercitrin (RT 6.33) and kaempferol-3-O-glucoside (RT 6.82). Photo-induced green synthesis of silver nanoparticles was reported in Nycanthes arbor-tristis. Nanoparticles were efficiently synthesized after mixing of 1% ethanol leaf extract and 1 mM silver nitrate solution under 10 min light exposure at room temperature. The UV–Vis spectrum of the brown colored reaction mixture showed sharp surface plasmon resonance at 460 nm. It confirmed the biosynthesis of silver nanoparticles. Nanoparticles were characterized by using SEM, TEM, and EDX. The results suggest that synthesized nanoparticles lie in the range of 10–50 nm. XRD, SAED and AFM data confirmed the polycrystalline nature of biosynthesized nanoparticles. Silver nanoparticles exhibited strong antibacterial activity than extract. All bacterial clinical isolates were sensitive to nanoparticles. Methicilin resistant Staphylococcus aureus was most susceptible than other isolates. The silver nanoparticles also exhibited good free radical scavenging activity (EC50 670.67 ± 15.70 µg/ml). © 2019, Springer Science+Business Media, LLC, part of Springer Nature.